From K-12 to MATATAG: A Systematic Review of the Factors Driving Curriculum Transition - Cabaya, Jelargen D.; Gerios, Cloyd Q.; Lano, Jeremiah B.; Valenzuela, Elmelyn B.; Sumayo, Gideon S. (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This systematic review examines the shift of Philippine curriculum from K-12 to the MATATAG. It aims to identify the key factors that drive this curriculum change, analyze perceptions from different education stakeholders, and assess how the MATATAG curriculum addresses the limitations found in the previous system. Methodology: Using the PRISMA framework, 25 relevant studies from 2020-2025 were analyzed thematically. Main Findings: Results reveal that systemic challenges such as content overload, weak foundational skills, and inadequate teacher training prompted the shift. Stakeholders generally support MATATAG for its streamlined competencies and contextual relevance, although issues in the implementation persist. Novelty/Originality of this study: Unlike earlier reviews that only describe the K-12 challenges or the policy intent of MATATAG, this study integrates both stakeholder perspectives and thematic analysis across multiple recent studies. By mapping how the MATATAG framework directly responds to previously documented limitations, it provides an evidence-based lens for anticipating long-term effects. This unique synthesis offers actionable insights for curriculum planners, policymakers, and teacher professional development programs seeking to align reforms with ground-level realities.